2019
DOI: 10.4103/ijnm.ijnm_98_19
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic value of pretreatment gallium-68 DOTATATE positron emission tomography/computed tomography in irradiated non-benign meningioma

Abstract: Purpose of the study:The purpose of this study was to evaluate the potential value of gallium-68 (Ga-68)-DOTATATE positron emission tomography/computed tomography (PET/CT) in predicting the risk of progression in nonbenign meningioma after definite irradiation. We retrospectively reviewed our patients with meningiomas who had the highest risk of progression: WHO histological Grade II and III tumors and with macroscopic disease as identified in Ga-68-DOTATATE PET/CT.Materials and Methods:Thirteen patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In order to effectively utilize [68Ga]-DOTATATE PET in the clinical context of meningioma, an SUV threshold that constitutes as the diagnostic threshold must be established. Prior studies often employed reference tissue SUVR approaches, such as contralateral brain parenchyma, contralateral subarachnoid space, liver, gluteal muscle, and superior sagittal sinus [4,5,[13][14][15]. One prospective study of 21 patients reported absolute SUV threshold of 2.3 with 90% sensitivity and 73% speci city for the purpose of diagnosing meningioma from tumor free tissue, which have been utilized in several other studies [5,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to effectively utilize [68Ga]-DOTATATE PET in the clinical context of meningioma, an SUV threshold that constitutes as the diagnostic threshold must be established. Prior studies often employed reference tissue SUVR approaches, such as contralateral brain parenchyma, contralateral subarachnoid space, liver, gluteal muscle, and superior sagittal sinus [4,5,[13][14][15]. One prospective study of 21 patients reported absolute SUV threshold of 2.3 with 90% sensitivity and 73% speci city for the purpose of diagnosing meningioma from tumor free tissue, which have been utilized in several other studies [5,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the speci city of [68Ga]-DOTATATE avidity in meningioma is affected by the variable physiologic uptake in other tissues including the pituitary, salivary, thyroid glands, liver, spleen, and urinary tract [12]. Several different methods have been utilized in previous studies to classify lesions as meningioma on the basis of [68Ga]-DOTATATE PET when interpreting standard uptake value (SUV) in meningioma, often with reference to SUV in a background tissue, such as contralateral brain parenchyma, contralateral subarachnoid space, liver, gluteal muscle, and superior sagittal sinus [4,5,[13][14][15]. While the liver reference recapitulates the Krenning score, rst established on the basis of Indium-111-Octreotide scintigraphic imaging, it does not re ect the differences in receptor speci city between [68Ga]-DOTATATE and Octreotide.…”
Section: Introductionmentioning
confidence: 99%
“…However if the patient is symptomatic or radiological progression occurs there are treatment options. These 'nonbenign menegioma's might be evaluated by means of Ga-68 DOTATATE PET/CT as a pretreatment imaging method [7]. This imaging modality has prognostic value in the preoperative imaging of this neoplasm which can predict risk of recurrence according to a previous study [7].…”
Section: Discussionmentioning
confidence: 99%
“…These 'nonbenign menegioma's might be evaluated by means of Ga-68 DOTATATE PET/CT as a pretreatment imaging method [7]. This imaging modality has prognostic value in the preoperative imaging of this neoplasm which can predict risk of recurrence according to a previous study [7]. Another study compared the value of intra arterial versus intravenous methods of Ga-68 DOTA imaging in patients with inoperable meningioma and achieved significantly increased accumulation [8].…”
Section: Discussionmentioning
confidence: 99%
“…The literature review describes SSTR expression and various DOTANOC positive meningioma,[ 8 9 ] detecting recurrence pattern on DOTA PET/CT scan,[ 10 11 ] predicting tumor growth. [ 12 ] The one limitation of the 68Ga-DOTANOC scan is the parasellar region because of the pituitary gland expressing SSTR2.…”
Section: Descriptionmentioning
confidence: 99%